The impact of nearly universal insurance coverage on health care utilization and health evidence from Medicare - Card, David E. (David Edward) 1956-; Dobkin, Carlos; Maestas, Nicole; National Bureau of Economic Research (Cambridge, Mass. National Bureau of Economic Research, 2004)
"We use the increases in health insurance coverage at age 65 generated by the rules of the Medicare program to evaluate the effects of health insurance coverage on health related behaviors and outcomes. The rise in overall coverage at age 65 is accompanied by a narrowing of disparities across race and education groups. Groups with bigger increases in coverage at 65 experience bigger reductions in the probability of delaying or not receiving medical care, and bigger increases in the probability of routine doctor visits. Hospital discharge records also show large increases in admission rates at age 65, especially for elective procedures like bypass surgery and joint replacement. The rises in hospitalization are bigger for whites than blacks, and for residents of areas with higher rates of insurance coverage prior to age 65, suggesting that the gains arise because of the relative generosity of Medicare, rather than the availability of insurance coverage. Finally, there are small impacts of reaching age 65 on self-reported health, with the largest gains among the groups that experience the largest gains in insurance coverage. In contrast we find no evidence of a shift in the rate of growth of mortality rates at age 65"--National Bureau of Economic Research web site.
Keywords: Medicare; Medical care -- United States